"If you don't stop the cycle somewhere, it just keeps going": Resilience in the context of structural violence and gender-based violence in rural Ontario. - Tara Mantler; Julia Yates; Katie J Shillington; Panagiota Tryphonopoulos; Kimberley T Jackson (Public Library of Science (PLoS), 2024)
Bolstering women's resilience in the context of gender-based violence (GBV) requires attention to structural conditions needed to support women to thrive, particularly in rural communities. This cross-sectional study explored how resilience was influenced by structural violence in rural Ontario among women experiencing GBV (n = 14) and service providers in the GBV sector (n = 12). Interviews were conducted and revealed forms of structural violence that undermine resilience for women experiencing GBV in rural communities, including 1) housing- gentrification, short-term rentals of residential properties, and long waitlists, 2) income- fighting for enough money to survive, 3) safety- abusers gaming the system, and 4) access- successes and new barriers. Structural conditions must be attended to as they are prerequisites required to build resilience.